Thinking About the Unthought Multiracial Subject: A Response to Adam Rodríguez's "Disallowing Multiplicity: Internalized Hierarchies, Dissociation, and Unformulated Bits of Self in a Poor, Mixed-Race Kid" - Brewster, Mary Kim (Psychoanalytic dialogues, 2024)
In responding to Adam Rodríguez's paper in this issue, I offer three autobiographical vignettes to depict aspects of my subjective experience of living as a multiracial person. Using his discussion of the multiracial subject as a point of departure, I consider how Asibong, Eng and Han, Stephens, and Mura conceptualize the racialized subject as socialized into carrying the harmful effects of racism for a White hegemonic system that is invested in erasing and forgetting its painful and violent history. I join Rodríguez in thinking about how a psychoanalytic treatment that combines an analysis of the racialized transference and countertransference, along with an exploration of the deleterious effects of the day-to-day racism experienced by the multiracial subject, opens possibilities to metabolize anger and guilt and mitigate the dissociation of aspects of the multiracial self.